PRODUCTS OF SUPEROXIDE IN THE THIN BOWEL OF RATS AT HYPO- AND HYPERMELATONINEMIYA - Anasevich, Ya.M.; Cebrzhins'kiy, O.I. (World of Medicine and Biology, 2010)
In a small intestine of rats each 30 days hypomelatoninemiya conducted production of increasment of superoxidanion radical from chains of powered and transported fagocyte, and each 30 days (the maintenance of rats in the dark and perorals melatonin introducted in a daily dose of weight of 1 mg/kg) hypermelatoninnemiya is from mitochondrial oxidation which is answers antioxidant to abilities of melatonin. Exit of superoxid from microsoming and power-transport chain of oxidation was not changed in both cases.